A methodology to screen priority toxins in pollutant release inventories - Moh Moh Thant Zin; Seong-Rin Lim (Journal of Environmental Management, 2023)

Environmental Effects of the Technology Transition from Liquid–Crystal Display (LCD) to Organic Light-Emitting Diode (OLED) Display from an E-Waste Management Perspective - Ji-Min Yeom; Hye-Jin Jung; Soo-Yeong Choi; Dae Sung Lee; Seong-Rin Lim (International Journal of Environmental Research, 2018)

Quantitative Sustainability Assessment of Seaweed Biomass as Bioethanol Feedstock - Hye Rim Park; Kyung A Jung; Seong-Rin Lim; Jong Moon Park (BioEnergy Research, 2014)

Linking Material Flow Analysis with Environmental Impact Potential - Carl W. Lam; Seong‐Rin Lim; Julie M. Schoenung (Journal of Industrial Ecology, 2013)
Summary Technology transition can have significant implications on the evolution of environmental impact potential of disposed electronics over time. Considering technology transition, we quantify the temporal behavior of ecological and human health impact potential from select heavy metals in electronic waste (e‐waste). The case study analyzes product substitution effects in two electronic cohorts from the U.S. market: (1) computers (laptops substituting for desktops) and (2) televisions (flat‐panel liquid crystal displays [LCDs] and plasma displays substituting for cathode‐ray tubes [CRTs]). Quantities of end‐of‐life (EoL) units to year 2030 are forecasted by the unique combination of dynamic material flow analysis, logistic trend analysis, and product lifespan calibration methods. Metal content from EoL units are assessed via a pathway and effect model using USETox™ characterization factors to determine the toxicity potential attributed to heavy metal releases into different media (e.g., air, water, and soil) as an indicator of environmental burden. Results show high impact materials such as lead, nickel, and zinc cause changes in human health toxicity potential and copper causes changes in ecological toxicity potential. Effects of dematerialization, such as reduced metal content in laptops over desktops, provide some positive benefits in toxicity potential per product. However, from a market perspective, emerging e‐waste quantities created by increasing per capita penetration rates of electronics and increasing population will offset gains in environmental performance at the product level. The resulting analysis provides guidance on the timing expected for emerging EoL units and an indication of high impact potential materials requiring pollution prevention as product substitution occurs.

Effects of Water Network Synthesis on the Air Pollutant Emissions and Energy Consumption of a Whole Economy - Seong-Rin Lim (Water, Air, & Soil Pollution, 2009)